Plastic physico-chemical properties shape the early marine plastisphere - Joanne M. Kingsbury; Olivier Laroche; Xavier Pochon; Anastasija Zaiko; Gavin Lear; Louise Weaver; Sally Gaw; Hayden Masterton; Fraser Doake; François Audrézet; Jessica Wallbank; Stefan D.M. Maday; et al. (Environmental Pollution, 2026)

An investigation into the stability and degradation of plastics in aquatic environments using a large-scale field-deployment study - Beatrix Theobald; Regis Risani; Lloyd Donaldson; James H. Bridson; Joanne M. Kingsbury; Olga Pantos; Louise Weaver; Gavin Lear; Xavier Pochon; Anastasija Zaiko; Dawn A. Smith; Ross Anderson; et al. (Science of The Total Environment, 2024)

Leaching and transformation of chemical additives from weathered plastic deployed in the marine environment - James H. Bridson; Hayden Masterton; Beatrix Theobald; Regis Risani; Fraser Doake; Jessica A. Wallbank; Stefan D.M. Maday; Gavin Lear; Robert Abbel; Dawn A. Smith; Joanne M. Kingsbury; Olga Pantos; et al. (Marine Pollution Bulletin, 2024)

A spatio-temporal analysis of marine diatom communities associated with pristine and aged plastics - Olivier Laroche; Olga Pantos; Joanne M. Kingsbury; Anastasija Zaiko; Jessica Wallbank; Gavin Lear; Jacob Thompson-Laing; Francois Audrezet; Stefan Maday; Fraser Doake; Robert Abbel; Maxime Barbier; et al. (Biofouling, 2023)

Into the Plastisphere, Where Only the Generalists Thrive: Early Insights in Plastisphere Microbial Community Succession - Jessica A. Wallbank; Gavin Lear; Joanne M. Kingsbury; Louise Weaver; Fraser Doake; Dawn A. Smith; François Audrézet; Stefan D. M. Maday; Victor Gambarini; Lloyd Donaldson; Beatrix Theobald; Maxime Barbier; et al. (Frontiers in Marine Science, 2022)
The ubiquity of plastic debris in marine environments raises the question, what impacts do plastics have on our marine microbiota? To investigate this, we applied bacterial 16S rRNA gene and fungal ITS2 region sequencing to identify changes in microbial biofilm community compositions on marine plastic, over time. We sampled biofilm on virgin linear low-density polyethylene (LLDPE), nylon-6 (PA) and glass after 2, 6 and 12 weeks of constant immersion in Te Whakaraupō-Lyttelton Harbour, Aotearoa-New Zealand. Of the prokaryotes, Proteobacteria and Bacteroidetes were predominant in all samples and Verrucomicrobiota were most abundant in mature biofilms. Microbial communities on the three substrate types were significantly distinct from those in the surrounding seawater, regardless of age, but not between attachment substrates. Bacterial communities occurring two weeks after immersion and fungal communities at six weeks were found to vary more among substrate types than at other times; however, no significant substrate-specific communities were identified overall. Taxa closely related to previously reported plastic-biodegrading species were found in very low abundance across all substrates, including on the glass slides. Our findings suggest that microorganisms do not selectively persist on the LLDPE or PA surfaces to gain significant direct metabolic benefit, instead using these plastics primarily as an attachment surface on which they form generalist biofilm communities.